IT Production: Monitoring Economic Security in Supply Chain Management - Svetlana Doguchaeva; Maksim Dombrovsky; Sergey Bratanovsky (International Journal of Supply Chain Management, 2019)
The rapid development of computer information technologies affected all spheres of human life. Therewith, unlawful distortion, falsification, destruction or disclosure of some information, as well as disorganization of information processing and transmission, cause serious material and moral damage to many subjects involved in the automated information interaction. The purpose of this research is to analyze the problems of economic security in distributed software development. In the legal practice of foreign countries, protection of computer programs is a controversial issue. This study involves a numerical analysis of the relationship between the International Property Rights Index (IPRI) and the Information and Communication Technology (ICT) Development Index. The analysis also touched upon the informal impact on economic security in the field of information and communication technologies. The correlation between the International Property Rights Index (IPRI) and the ICT Development Index (IDI) across countries is between 0.32 and 0.52. In the USA, Germany, Belgium, India,the correlation between the growth rate of IDI and the growth rate of IPRI is negative due to the high growth rates of IDI over striding the growth rates of IPRI. This article offers an innovative approach to the organization of block chain-based software development.